Menyemai Kedaulatan Pangan dari Sisi Pinggiran: UU Desa dan Marwah Pertanian dalam Pembangunan Pedesaan di Indonesia - Arie Sujito; Ghofur, Mohammad (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
After the enactment of the Village Law, the opportunity for the village as the spearhead of food sovereignty is widely open and the Village Law is considered a soul for village development. Village’s main activities are agriculture, including the management of natural resources with the composition of the area as a place for rural settlements, government services, social services, and economic activities. Most of the population works in the primary sector, which has various challenges to reducing or even eliminating dependence on the global food market. Rural development and the orientation of village agricultural soul so far seem to go hand in hand but tend to be particular. This study aimed to study the primary sector of agriculture and food needs as the main political discourse with the subject of the village. The study was prepared using a qualitative methodology with secondary data and policy analysis. The political economy framework is used to see how far the potential and challenges ahead are toward Indonesia's food sovereignty, amidst the onslaught of neo-liberalism in the global food system. The findings show that Village Law seeks to restore the village's dignity so that it becomes an empowered village faced with the unpreparedness of village capacity.